2018
DOI: 10.1101/282350
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sex differences in gene expression in response to ischemia in the human myocardium

Abstract: Word Count: 7520 (intro-conclusion (4028) + 60 citations (1951 words)). Abstract: 254 words 2 Abstract and Keywords Background: Sex differences exist in the prevalence, presentation, and outcomes of ischemic heart disease. Females have higher risk of heart failure post myocardial infarction relative to males and the female sex is an independent risk factor for hospital and operative mortality after cardiac surgery. However, the mechanisms underlying this sexual dimorphism remain unclear.We examined sex differe… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…As we observed depletion of eQTLs found in healthy individuals among the conserved response genes in our study, we next considered eQTLs found among CVD patients. To do so, we investigated the contribution of eQTLs identified in left ventricle heart tissue from patients undergoing aortic valve replacement surgery pre-and post-cardioplegic arrest and ischemia, to our hypoxia response categories (Stone et al 2018). Again, we observed a depletion of eGenes in the conserved response category for both pre-and post-ischemia eGenes (P = 0.03 and P =0.006 respectively; Figure S16A).…”
Section: Properties Of Conserved Hypoxic Response Genesmentioning
confidence: 95%
See 1 more Smart Citation
“…As we observed depletion of eQTLs found in healthy individuals among the conserved response genes in our study, we next considered eQTLs found among CVD patients. To do so, we investigated the contribution of eQTLs identified in left ventricle heart tissue from patients undergoing aortic valve replacement surgery pre-and post-cardioplegic arrest and ischemia, to our hypoxia response categories (Stone et al 2018). Again, we observed a depletion of eGenes in the conserved response category for both pre-and post-ischemia eGenes (P = 0.03 and P =0.006 respectively; Figure S16A).…”
Section: Properties Of Conserved Hypoxic Response Genesmentioning
confidence: 95%
“…The gene sets belonging to each of the four response categories were investigated for common pathway enrichment using the KEGG database (Kanehisa et al 2017 For the overlap of our response categories with eQTLs identified pre-and post-ischemia, an RNAseq study of 114 patients undergoing aortic valve replacement surgery was used (Stone et al 2018). In this study, samples of heart left ventricle were obtained for each individual pre-and postcardioplegic arrest/ischemia.…”
Section: Gene Ontology Analysismentioning
confidence: 99%
“…4 One such example is that females express genes associated with ischemic events which correlates with their higher risk of developing post-myocardial infarction relative to males. 5 Second, many neurological disorders also exhibit sex differences in incidence, severity, or response to treatment. For example, the hormone estrogen provides protective effects to the blood-brain barrier, making females less susceptible to neuroinflammatory disorders relative to males.…”
Section: Introductionmentioning
confidence: 99%